Albania : Ninth and Tenth Reviews Under the Extended Arrangement, and Proposal for Post-Programmonitoring-Press Release; Staff Report; and Statement by the Excutive Director for Albania. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Albania's Ninth and Tenth Reviews under the Extended Arrangement and Proposal for Post-Program Monitoring. All performance criteria were met, although of the three indicative targets were missed by a narrow margin. Eleven structural benchmarks were also implemented. Over the past three years, the authorities have met most quantitative targets and have made good progress in implementing the structural reform agenda under the program, albeit with some delays. The IMF staff supports the completion of the Ninth and Tenth Reviews under the Extended Arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet